New Normal as an Opening Door to State Financial Stability through the Post-PSBB Tourism Sector - Fitria Esfandiari; Duflitama Astesa; Ganisha Sidiq Pramono; Tivania Rachmaudina Lavia Ridha; Maualana Nurhafidz Maskat; Syamil Abdurrahim (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
As a country affected by the Covid-19 pandemic, it has become a special note for the Indonesian government to make a policy so that the spread of Covid-19 can be overcome. One of the policies made by the Indonesian government is the implementation of PSBB (Large-Scale Social Restrictions) in several affected areas. The impact of the application is none other than attacking various sectors of life, especially on the speed of state finances which are experiencing a decline. Therefore, the presence of the New Normal as a post-PSBB transition is used as an